Exploring the Role of Project-Based Learning in Enhancing Non-Profit Accounting Competencies: Evidence from Public Financial Accounting Students at Bengkalis State Polytechnic - Muttaqin, Husnul; Astari, Yanisha Dwi; Asfina, Risda; Rosmala, Mira (Jurnal EMT KITA, 2026)
Non-profit organizations require accountants who are not only technically competent but also capable of managing accountability, donor restrictions, and ethical responsibilities. However, non-profit accounting remains underrepresented in many accounting curricula, including public financial accounting programs. This study aims to examine the role of Project-Based Learning (PBL) in non-profit accounting education by exploring students’ perceptions of PBL, its contribution to their understanding of non-profit accounting practices, and its influence on perceived career readiness. The study employed a descriptive quantitative approach using survey data collected from 71 undergraduate students enrolled in the Public Financial Accounting Study Program at Bengkalis State Polytechnic. Data were analyzed using descriptive statistical techniques to capture patterns in students’ responses. The results indicate that students perceive PBL as an effective and appropriate learning approach for non-profit accounting. PBL was found to support students’ understanding of key accounting concepts, facilitate the application of non-profit accounting practices through project tasks, and enhance students’ confidence and perceived readiness for future careers in the non-profit and public sectors. The findings suggest that integrating PBL into non-profit accounting courses can strengthen the alignment between academic learning and professional demands. This study provides empirical support for the use of PBL as a core instructional strategy in non-profit accounting education and offers insights for curriculum development in public financial accounting programs.